Analysing nonsynonymous mutations between two Mycobacterium bovis strains with contrasting pathogenic profiles - Bigi, María Mercedes; Vazquez, Cristina Lourdes; Castelão, Ana Beatriz C.; Garcia, Elizabeth Andrea; Cataldi, Angel Adrian; Jackson, Mary; McNeil, Michael; Soria, Marcelo Abel; Zumarraga, Martin Jose; Cabruja, Matias; Gago, Gabriela; Blanco, Federico Carlos; et al. (Elsevier, 2020)
Mycobacterium bovis (M. bovis) is the causative agent of bovine tuberculosis, a chronic infectious disease that can affect cattle, other domesticated species, wild animals and humans. This disease produces important economic losses worldwide. Two M. bovis strains (04-303 and 534) have been isolated in Argentina. Whereas the 04-303 strain was isolated from a wild boar, the 534 strain was obtained from cattle. In a previous study, six weeks after infection, the 04-303 strain induced 100% mortality in mice. By contrast, mice infected with the 534 strain survived, with limited tissue damage, after four months. In this study we compared all predictive proteins encoded in both M. bovis genomes. The comparative analysis revealed 141 polymorphic proteins between both strains. From these proteins, nine virulence proteins showed polymorphisms in 04-303, whereas five did it in the 534 strain. Remarkably, both strains contained a high level of polymorphism in proteins related to phthiocerol dimycocerosate (PDIM) synthesis or transport. Further experimental evidence indicated that only mutations in the 534 strain have an impact on PDIM synthesis. The observed reduction in PDIM content in the 534 strain, together with its low capacity to induce phagosome arrest, may be associated with the reported deficiency of this strain to replicate and survive inside bovine macrophages. The findings of this study could contribute to a better understanding of pathogenicity and virulence aspects of M. bovis, which is essential for further studies aiming at developing new vaccines and diagnostic techniques for bovines.